Overview of Palliative Care - Paudel, B D; Dangal, G; Munday, D (Nepal Journal of Obstetrics and Gynaecology, 2014)
Patients diagnosed with a life threatening condition like cancer suffer physically, socially and mentally. Their quality of life can be improved by effective communication and good symptom control even when the disease is incurable. Pain is the most common symptom and can be controlled by optimal use of analgesics especially oral morphine if severe. Psychosocial issues like depression and anxiety can be minimized by counseling and use of medicines. Death is more painful than birth but can be minimized by understanding the reality and by honest sharing which will help to minimize unnecessary sufferings. Palliative care is the care of these patients and their family members to make their life comfortable. Modern palliative care has developed around the world since the 1960s and in Nepal, since the beginning of 21st century. Much remains to be done before palliative care can be an integrated part of health care in Nepal. In this context gynaecologist having knowledge and skills in palliative care, have an important role in improving the quality of life of patients with life threatening condition and their family members. DOI: http://dx.doi.org/10.3126/njog.v9i2.11724